Volume Management in the Critically Ill Patient with Acute Kidney Injury - Mary Labib; Raeesa Khalid; Akram Khan; Supriya Khan (Critical Care Research and Practice)
Acute kidney injury (AKI) frequently occurs in the setting of critical illness and its management poses a challenge for the intensivist. Optimal management of volume status is critical in the setting of AKI in the ICU patient. The use of urine sodium, the fractional excretion of sodium (FeNa), and the fractional excretion of urea (FeUrea) are common clinical tools used to help guide fluid management especially further volume expansion but should be used in the context of the patient’s overall clinical scenario as they are not completely sensitive or specific for the finding of volume depletion and can be misleading. In the case of oliguric or anuric AKI, diuretics are often utilized to increase the urine output although current evidence suggests that they are best reserved for the treatment of volume overload and hyperkalemia in patients who are likely to respond to them. Management of volume overload in ICU patients with AKI is especially important as volume overload has several negative effects on organ function and overall morbidity and mortality.